Princess Kiko of Japan - O'Shei, Tim. (Mankato, Minn. : Capstone Press, 2009)
Describes the life of Princess Kiko of Japan, discussing her childhood, education, marriage to Prince Aya, royal duties, and children.
Includes bibliographical references (p. 31) and index.
3.6
5-8
Keywords: Kiko, -- Princess of Japan, -- 1966- -- Juvenile literature; Princesses -- Japan -- Biography -- Juvenile literature; Akishino no Miya Fumihito, -- Prince, son of Akihito, Emperor of Japan, -- 1965- -- Juvenile literature; Kiko, -- Princess of Japan, -- 1966-; Princesses; Women -- Biography; Akishino no Miya Fumihito, -- Prince, son of Akihito, Emperor of Japan, -- 1965-; Kiko, -- Princess of Japan, -- 1966-; Princesses -- Biography; Women -- Biography; Akishino no Miya Fumihito, -- Prince, son of Akihito, Emperor of Japan, -- 1965-